Correlation between Achievement Motivation and Reading Comprehension Ability through Science Literacy to High School Students - Sri Wahyuni; Mieke Miarsyah; Adisyahputra Adisyahputra (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The research is to know the relationship between achievement motivation (X1), and reading comprehension ability (X2) with science literacy ability of high school students (Y). The data is all students of class X SMA Negeri 9 Jakarta. Based on data analysis can be known coefficient correlation between X1 with Y is 0,326 correlation coefficient between X2 with Y is 0,392 and correlation coefficient between X2and X1with Y is 0,601. The motivation of pace, and the ability to read the students understanding contribute 36,1% to the literacy ability of high school students. Keywords: Achievement motivation, critical thinking, reading comprehension, science literacy